2018
DOI: 10.1242/jcs.214544
|View full text |Cite
|
Sign up to set email alerts
|

Activated ezrin controls MISP levels to ensure correct NuMA polarization and spindle orientation

Abstract: Correct spindle orientation is achieved through signaling pathways that provide a molecular link between the cell cortex and spindle microtubules in an F-actin-dependent manner. A conserved cortical protein complex, composed of LGN (also known as GPSM2), NuMA (also known as NUMA1) and dynein-dynactin, plays a key role in establishing proper spindle orientation. It has also been shown that the actin-binding protein MISP and the ERM family, which are activated by lymphocyte-oriented kinase (LOK, also known as ST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
20
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 79 publications
(131 reference statements)
5
20
0
Order By: Relevance
“…Thus, Merlin may influence mitotic progression by modulating Ezrin functions. Interestingly, it was also reported that a correct polarized localization of NuMa is necessary for proper spindle orientation in mitosis and requires the local activation of Ezrin by the Slk kinase (39). The expression of a constitutively active form of Ezrin leads to an unpolarized recruitment of NuMa and a defect in spindle orientation in mouse apical progenitor, resulting in the same spindle orientation defect that we observed in Hela cells expressing the Merlin AA mutant.…”
Section: Discussionsupporting
confidence: 75%
“…Thus, Merlin may influence mitotic progression by modulating Ezrin functions. Interestingly, it was also reported that a correct polarized localization of NuMa is necessary for proper spindle orientation in mitosis and requires the local activation of Ezrin by the Slk kinase (39). The expression of a constitutively active form of Ezrin leads to an unpolarized recruitment of NuMa and a defect in spindle orientation in mouse apical progenitor, resulting in the same spindle orientation defect that we observed in Hela cells expressing the Merlin AA mutant.…”
Section: Discussionsupporting
confidence: 75%
“…For indirect IF HeLa, U2OS, HEK293T, and RPE1 cells were treated as described previously (Cizmecioglu et al , 2010; Kschonsak and Hoffmann, 2018). Coverslips were mounted onto glass slides with ProLong Gold (Molecular Probes) or Mowiol (Calbiochem).…”
Section: Methodsmentioning
confidence: 99%
“…The PKC isoenzymes PKC-θ and PKC-α phosphorylate moesin and ezrin in vitro and associate with them in human T lymphocytes and breast carcinoma cells, respectively [44,45]. Moreover, recent attention has been given to germinal center kinases (GCK), a subfamily of the mammalian sterile 20-like kinases (Mst) including lymphocyte-oriented kinase (LOK), Mst4, SLK and Nck interacting kinase (NIK), as the main kinases that phosphorylate the regulatory Thr of ERMs during cell motility and division [46][47][48][49][50][51]. To this list of kinases, we must now add two sterile 20-like kinases identified in Drosophila, misshapen (an orthologue of NIK) and Slik/SLK [52][53][54].…”
Section: Erm Tools For Plasma Membrane-to-cytoskeleton Bridgingmentioning
confidence: 99%